Tata Kelola Perusahaan yang Baik Terhadap Manajemen Laba pada Badan Usaha Milik Negara Indonesia yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2021 - Sri Rahayu (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This The neglect of the principles of Good Corporate Governance in all aspects of the life of the nation and state is one of the most fundamental factors that triggers the occurrence of a multi-dimensional crisis in Indonesia. To achieve maximum corporate value, management and shareholders are expected to be able to synergize to realize good corporate governance. This study aims to analyze good corporate governance on earnings management in Indonesian State-Owned Enterprises listed on the Indonesia Stock Exchange. The quantitative approach becomes a research method with secondary data as a source of research data obtained by researchers indirectly through intermediary media. Internal data collection techniques are literature studies or the use of documents as secondary data sources in quantitative research. The data analysis technique used descriptive statistics. Descriptive statistics aim to provide a summary of the data sample and do not use the data to make conclusions on the population. The results show that the Covid-19 pandemic that has occurred in the world has also affected the investment world in Indonesia. Since the Covid-19 case, the trend of the Composite Stock Price Index has decreased. Fluctuations in the capital market affect people's behavior in investing because analyzing the capital market is not just looking at numbers, but also looking at the behavioral financial or economic aspects of investors' behavior. Percentage Change in Public Consumption of the 5 highest consumer goods are health products, food ingredients, credit or data packages, ready-to-eat food and beverages, the 3 consumption goods are the outputs of companies in the consumer goods industry sector. Good corporate governance is an important component of a company's lasting success.